2010
DOI: 10.1080/09064702.2010.488270
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to incidence of spontaneous oxidized flavor and copper in cow's milk

Abstract: The incidence of spontaneous oxidized flavor (SOF) is commonly assumed to be dependent on the combination of substrate supply and contents of pro-and anti-oxidants in milk. A total of 142 cows in the experimental herd at the Swedish University of Agricultural Sciences were included, 87 of the Swedish Red breed and 55 of the Swedish Holstein breed. Altogether 893 milk samples were analyzed for milk composition, copper content, and milk flavor. Milk copper concentration was highest in early lactation and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…Copper can directly react with triplet state oxygen and phenol compounds to generate reactive oxygen species and play a major role in the decomposition of hydroperoxides formed in the propagation step of autoxidation (Kochhar ; Kanner ). The origin of spontaneous oxidized flavor has not been identified in milk, but its occurrence has been linked to genetic predisposition and the concurrent presence of polyunsaturated fatty acids and high levels of copper in milk (Granelli and others ; Juhlin and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Copper can directly react with triplet state oxygen and phenol compounds to generate reactive oxygen species and play a major role in the decomposition of hydroperoxides formed in the propagation step of autoxidation (Kochhar ; Kanner ). The origin of spontaneous oxidized flavor has not been identified in milk, but its occurrence has been linked to genetic predisposition and the concurrent presence of polyunsaturated fatty acids and high levels of copper in milk (Granelli and others ; Juhlin and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The off-flavor was first identified in northern Europe, and during the last decade it has been recognized as a growing problem in the Midwest-ern United States. It has been frequently described as a seasonal off-flavor taint, appearing in the late autumn months and disappearing in early spring (Juhlin et al, 2010a). Because the associated objectionable flavors are reminiscent of lipid oxidation and affect the flavor of clean milk, a common assumption is an oxidative radical mechanism is responsible, hence the name SOF.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have frequently attempted to correlate SOF sensory defects with changes in known causative factors associated with oxidative reaction pathways. The most common examples include changes in bovine diet, such as the presence of specific PUFA, as well as other factors that affect instigation or inhibition of SOF through various oxidizers, antioxidants, catalysts, and so on (Dunkley et al, 1963;Bruhn et al, 1976;Juhlin et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Genetics of cows has been mentioned as an influence on the occurrence of SOF in milk (Juhlin et al, 2010b). Additionally, Juhlin et al (2010a) found that copper ion concentration in milk from first lactation cows (one to three weeks postpartum) was significantly linked to development of SOF. In our study, we used both primparous and multiparous mid-lactation dairy cows; so, no direct comparison can be made.…”
Section: Peroxide Value and Free Fatty Acid Contentmentioning
confidence: 99%
“…The DDGS used in this study was not responsible for SOF in milk. Additionally, because our cows were mid-lactation and were primiparous and multiparous rather than fresh first-lactation cows, we cannot discount SOF that may appear if this experiment was repeated by using first-lactation transition cows, which produce milk with more copper ions (Juhlin et al, 2010a). Future studies, however, would need to be done to address the question of the occurrence of SOF in early lactation.…”
Section: Peroxide Value and Free Fatty Acid Contentmentioning
confidence: 99%